Lyophilized Escherichia coli strains stored for 40–50 years: morphological, serotypic, biochemical characteristics and drug sensitivity - Neli Ermenlieva; Emilia Georgieva; Gabriela Tsankova; Gergana Nedelcheva; Krasimira Laleva; Sylvia Stamova; Todorka Kostadinova (Biotechnology & Biotechnological Equipment)
Bacterial cultures are commonly preserved for long periods of time via freeze-drying (lyophilization). Lyophilized bacteria typically retain viability from 5 to 35 years. We investigated the vitality and preservation of some of the characteristic morphological, serotypic and biochemical features of 14 Escherichia coli strains following lyophilized storage for over 40–50 years. We also investigated their susceptibility to conventional antibiotics used in the therapy of infections caused by Enterobacteriaceae representatives. In our study, 14 strains of E. coli related to 11 serological types – O1, O2 (two strains), O5, O7, O11, O20, O25, O26, O29, O111 (two strains) and O125 (two strains) – were used. The lyophilized microorganism ampules were produced in the period of 1971 to 1973 and were stored at 4 °C in a microbial collection for educational purposes at the Medical College – Varna, Bulgaria. Control strains were E. coli ATCC25922, an E. coli strain (used for educational purposes) and three clinical E. coli isolates from urine and wound secretions. The E. coli strains stored for 40–50 years had preserved the studied morphological and biochemical characteristics, as well as those related to their antigenic characteristics and antibiotic sensitivity. Their susceptibility to the tested antimicrobials was analogical to the control reference strain E. coli ATCC25922, indicating that despite the long storage time, all strains retained and demonstrated the typical morphological, stereotypic and biochemical characteristics of the species.